Mental Health Patterns and Consequences : Results from Survey Data in Five Developing Countries - Das, Jishnu; Do, Quy-Toan; Friedman, Jed; McKenzie, David (World Bank, Washington, DC, 2012)
The social and economic consequences of poor mental health in the developing world are presumed to be significant, yet are largely under-researched. The authors argue that mental health modules can be meaningfully added to multi-purpose household surveys in developing countries, and used to investigate this relationship. Data from nationally representative surveys in Bosnia and Herzegovina, Indonesia, and Mexico, along with special surveys from India and Tonga, show similar patterns of association between mental health and socioeconomic characteristics across countries. Individuals who are older, female, widowed, and report poor physical health are more likely to report worse mental health outcomes. Individuals living with others with poor mental health are also significantly more likely to report worse mental health themselves. In contrast, there is little observed relationship between mental health and poverty or education, common measures of socio-economic status. The results instead suggest that economic and multi-dimensional shocks such as illness or crisis can have a greater impact on mental health than overall levels of poverty. This may have important implications for social protection policy. The authors also find significant associations between poor mental health and lowered labor force participation (especially for women) and higher frequency visits to health centers, suggesting that poor mental health can have significant economic consequences for households and the health system. Finally, the paper discusses how measures of mental health are distinct from general subjective welfare measures such as happiness and indicate useful directions of future research.